2017
DOI: 10.17159/2309-8309/2017/v16n1a4
|View full text |Cite
|
Sign up to set email alerts
|

Gunshot tibia fractures treated with intramedullary nailing: A single centre retrospective review

Abstract: Background: Open tibia fractures are notoriously difficult to treat, with a high rate of union problems and infection. Gunshot wound-associated fractures of the tibia compound these issues further by causing extensive bone comminution and soft tissue damage. No universally accepted management protocol exists, but intramedullary (IM) nailing of these injuries is an attractive treatment strategy. It provides stable internal fixation and limits further insult to the soft tissue envelope. It also allows complete a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…IMN fixation showed outcomes comparable to a previous publication by Hilton et al who reported a 76.9% initial union rate following intermedullary nailing for gunshot tibial shaft fractures, with three patients developing osteomyelitis. 8 The union rate observed in the present study for IMN was 91%.…”
Section: Discussionsupporting
confidence: 43%
See 3 more Smart Citations
“…IMN fixation showed outcomes comparable to a previous publication by Hilton et al who reported a 76.9% initial union rate following intermedullary nailing for gunshot tibial shaft fractures, with three patients developing osteomyelitis. 8 The union rate observed in the present study for IMN was 91%.…”
Section: Discussionsupporting
confidence: 43%
“…The first finding of this study was the demographic sample and the predominant involvement of young males (89% male with a mean age of 29.2±10.2 years), which is similar to previous published reports on orthopaedic injuries following civilian gunshots. 3,6,8 A recent study conducted in South Africa reported a higher rate of intentional and gang-related violence together with the use of alcohol and illegal drugs among young, gunshot-injured males. 5 While we did not test patients for alcohol or illegal drugs in the present study, our finding, together with the previous reports, again highlights this group of individuals to be a potential target for intervention in the future.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An alternative classification by Long et al [5], specifically designed for gunshot-associated femur fractures, may be a more appropriate accounting for both the physical wound characteristics and the radiographic zone of injury of both the skin and soft tissue, as well as the degree of comminution. One study [2] suggested that the radiographic zone of comminution should be considered as important as the size of the soft tissue wound when determining treatment, with a trend toward an increased risk of infection when the radiographic zone of comminution exceeded 120 mm. The authors cautioned, however, that strong consideration should be given to external fixation for fractures with zones in excess of 120 mm as a way to minimize complications.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%